Metabolic disturbances in acute pancreatitis: mechanisms and therapeutic implications - Fang, Chao; Ding, Yingwei; Wang, Xiaojun; Teng, Xusheng (Frontiers in Endocrinology, 2025)
Acute pancreatitis (AP) is a common inflammatory condition of the pancreas that is often associated with metabolic disturbances resulting from pancreatic injury. This review examines the intricate relationship between metabolic abnormalities, such as changes in lipid and glucose metabolism, and the pathophysiology of AP. While these metabolic disturbances do not directly cause AP, they can significantly worsen the progression and severity of the disease. For instance, hypertriglyceridemia can increase pancreatic necrosis through mechanisms like lipotoxicity and oxidative stress. Similarly, disorders in glucose metabolism can further damage pancreatic cells by heightening inflammatory responses and oxidative stress. Additionally, we investigate novel metabolic interventions, including lipase inhibitors, insulin therapy, and antioxidants, designed to address these metabolic disturbances and reduce the severity of the disease. Understanding how metabolic disturbances contribute to the progression of AP is crucial for developing effective therapeutic strategies and improving patient outcomes.